Caracterização e estabelecimento de um novo método para a purificação de uma protease de 60 kDa da secreção de cercária de Schistosoma mansoni - Tulio Marcos Santos (1995)
The acetabular glands of the Schistosoma mansoni cercaria produce a secretion which is involved in the penetration process of this parasite into the vertebrate host skin. This secretion contains proteases that degrade macromolecules from the skin matrix, help to remove the glicocalix layer and in the transformation from cercaria into schistosomulum, and also induce cutaneous hypersensitivity reaction. An antigenic fraction able to induce histamine release from mastocytes was obtained previously by our group after passing a semi-purified fraction from cercaria secretion into a column which contained IgGs from mice chronically infected with S. mansoni bound to Sepharose beads. The antigenic fraction contained a 60 kDa enzyme as its main component that, nevertheless, was not completely purified yet. To conclude the biochemical and immunological characterization of this enzyme, we established in this work a new method for its purification. Gel filtration, immunoaffinity, and ion exchange were the chromatographic steps employed. The 60 kDa enzyme isolated is a serine protease, (inhibited mostly by TLCK and TPCK) that degrades collagen components from the skin. Its optimum activity is at 40 oC and at pH 8.0. Its activity is not stimulated in the presence of Ca2+. The enzyme is a glycoprotein but the carbohydrate in its structure does not contain manose. The carbohydrate portion of the 60 kDa protease purified from cercarial secretions is its main immunogenic component showing by ELISA strong reaction with serum from mouse chronically infected with S. mansoni.